Accurate Determination of Qibla Direction: A Comparative Study of Haversine, Vincenty, Spherical Trigonometry, Great Circle Navigation, and Equatorial Oblique Cylindrical Projection Algorithms using Python Programing Language (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Determining the direction of the Qibla, which points towards the Kaaba in Mecca, is an essential requirement for Muslims during their daily prayers. With the advent of modern computational techniques, various algorithms have been developed to calculate the Qibla direction accurately. This paper presents a comparative study of five widely used algorithms: the Haversine formula, Vincenty's formula, the Spherical Trigonometry method, the Great Circle Navigation method, and the Equatorial Oblique Cylindrical Projection method. We provide a detailed explanation of all five algorithms, highlighting their underlying principles, mathematical formulations, and implementation details using python programing language. Additionally, we analyze the accuracy and performance trade-offs between these methods, enabling users to make informed decisions based on their specific requirements. Also, to evaluate the performance of the algorithms, 300 random locations were generated on the map using Python.